(untitled) (Italian Review of Legal History, 2015)
This essay illustrates the varied relationship between the city of Casale and the University of Pavia as the main center for law studies of the Monferrato élites in the 14th and 15th centuries. As these scholars return to their homeland after studying in Pavia, the skills and the education obtained at the University allow them to aspire to the highest political and institutional positions of the State, as Senators and Presidents of the “Senatus Montisferrati”. In so doing, the essay explores the dynamic relationship between the Senate of Casale and so peculiar a Jurisprudence, that it indeed deserves the definition of ” casalese”.